Implementasi Metode Amtsilati Dalam Meningkatkan Pemahaman Santri Pada Pembelajaran Nahwu - Fauzi; iman saifullah; ahmad jaelani (Yayasan Al-Afif, 2024)
In the reality and dynamics of learning in Islamic boarding schools, students often experience difficulties when learning the science of nahwu, this matter. The importance of an effective learning method in studying nahwu science is because the right method can help students in solving the challenges they face. One of the good learning methods that can facilitate students' understanding of concepts in nahwu science is the Amtsilati method which teaches learning in systematic and logical steps. The approach in this research uses a descriptive qualitative approach. Qualitative descriptive means researchers describe symptoms, events, real phenomena as they exist when the research is in progress. Data collection methods use interviews, observation and documentation. Amtsilati has been implemented at the Darul Falah Amtsilati Garut Islamic Boarding School, as a method for learning nahwu through several stages, namely: planning, process and learning evaluation. Second, students' understanding of nahwu learning. Third, the advantages and disadvantages of learning nahwu science using the Amtsilati method.